AN ANALYSIS SUBTITLYING STRATEGIS OF SPIDERMAN 2 FILM - Lukito Mulyono, - (2007)
The title of this paper is "An Analysis of Subtitling Strategies of Spider-Man 2 Film." This paper presents an analysis of subtitling strategies, reasons behind the use of the subtitling strategies, and problems faced by the subtitler in subtitling Spider-Man 2 film. Qualitative research design in the form of a case study is used in this research. The data are collected from the Internet, library, correspondences with the production house, the subtitler, and an original VCD of Spider-Man 2. The data are analyzed based on the subtitling theories proposed by Gottlieb (Taylor, 2000) and Niska (Niska, 2003). It is revealed that, from Gottlieb's viewpoint, nine strategies are used. Meanwhile, from Niska's viewpoint, six strategies are used. rt is also revealed that there are several reasons behind the use of each strategy mainly concerning accuracy and efficiency. Eight technical and non-technical problems are identified from the analysis and it is concluded that Gottlieb's and Niska's strategies have their own distinctive strengths.